2017
DOI: 10.5935/0004-2749.20170044
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal assessment of patients with chronic central serous chorioretinopathy

Abstract: In patients with chronic CSC, ICG may reveal choroidal abnormalities that are not evident on FA. This finding may help optimize the monitoring and treatment of CSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although we did not perform indocyanine green angiography, it is an important tool to detect choroidal changes and discriminate between these entities. Viana et al (5) studied the ICG and FA pattern in patients with chronic CSC, and demonstrated that, in the early phases, the ICG displays hyperfluorescent areas that do not appear in the FA due to increased choroidal permeability, which suggest that ICG is more sensitive than FA for detecting choroidal abnormalities in these cases. In contrast, Gharbiya et al (6) demonstrated that, in the early phase of ICG, patients with SLE choroidopathy presented with hypofluorescent areas that become hyperfluorescent in the intermediate to late phases.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not perform indocyanine green angiography, it is an important tool to detect choroidal changes and discriminate between these entities. Viana et al (5) studied the ICG and FA pattern in patients with chronic CSC, and demonstrated that, in the early phases, the ICG displays hyperfluorescent areas that do not appear in the FA due to increased choroidal permeability, which suggest that ICG is more sensitive than FA for detecting choroidal abnormalities in these cases. In contrast, Gharbiya et al (6) demonstrated that, in the early phase of ICG, patients with SLE choroidopathy presented with hypofluorescent areas that become hyperfluorescent in the intermediate to late phases.…”
Section: Discussionmentioning
confidence: 99%
“…The above process has completed the green production method of products based on the environmental protection management and ecological perspective of the enterprise, preventing and controlling the environmental pollution caused by production from two aspects of raw material selection and product production process, and completing the green production of products (Viana et al, 2017).…”
Section: Waste Treatmentmentioning
confidence: 99%
“…However, ICGA is expensive and time-consuming, and the required device is less available than the device that executes FA. [ 9 ] Limited studies have suggested similar efficacy for these two imaging modalities to guide PDT in patients with CSC. [ 10 , 11 ] This study was performed to compare the outcomes of ICGA-guided half-dose PDT with those of FA-guided half-dose PDT in patients with chronic CSC.…”
Section: Introductionmentioning
confidence: 99%